Value Creation in Nigerian Listed Consumer Goods Firms through Entrepreneurial Cash Management - Muojekwu, Hilary Onyebuchi; Ochuka, Chekwube Esther; Nworie, Gilbert Ogechukwu (PT Mattawang Mediatama Solution, 2025)
Firms that fail to embrace entrepreneurial cash management often miss critical growth opportunities, underperform in volatile markets, and struggle to meet investor expectations for long-term value. In Nigeria’s challenging financial environment, overreliance on traditional cash management undermines agility, innovation, and financial resilience, leaving listed consumer goods firms vulnerable to stagnation, competitive decline, and underperformance in the capital market unless they adopt entrepreneurial approaches to managing cash as a strategic asset. This study is therefore necessitated by the need to examine how entrepreneurial cash management (proxy by cash level of firm) on corporate value creation (proxy by firm value-added) in Nigerian consumer goods sector. Ex-post facto research design was deployed on a population of 20 listed consumer goods firms. Purposive sampling was used to select a sample size of 15 firms. Secondary data were gleaned from the annual reports of the firms over a ten year period (2015-2024). In addition to descriptive analysis and other model diagnostics, the hypothesis was tested using panel estimated generalised least squares. The finding revealed that entrepreneurial cash management (indexed by cash level of firm) has a significant positive effect on corporate value creation (indexed by firm value-added) in Nigerian consumer goods sector (β = 0.564707, p = 0.0000). In conclusion, in an environment characterized by fluctuating macroeconomic indicators, high financing costs, and market volatility, internally generated liquidity emerges as a vital entrepreneurial asset that enables firms to create sustainable economic value. The study recommends that Chief Financial Officers (CFOs) of need to institutionalize entrepreneurial cash management systems that emphasize strategic liquidity optimization as a deliberate value-creation mechanism by adopting dynamic cash flow forecasting tools, scenario analysis, and contingency planning frameworks that are proactive and data-driven.